Long-Term Results of Simultaneous Bilateral External Dacryocystorhinostomy in Cases with Bilateral Dacryostenosis*. (January 2015) - Yuksel, Dilek; Kosker, Mustafa; Akoz, Irem; Simsek, Saban
ABSTRACT Objectives: To evaluate the long-term results of simultaneous bilateral external dacryocystorhinostomy (EX-DCR) in cases with bilateral dacryostenosis. Methods: Thirty-four eyes of 17 consecutive patients with a history of bilateral epiphora were included in the study between 2007 and 2011. Demographic information, etiology of the obstruction, history of lacrimal surgery, type of anesthesia, duration of surgery, incidence of postoperative nasal bleeding and infection, surgical outcomes, and duration of follow-up were recorded. During the lacrimal irrigation, there was not any passage noticed in the patients' eyes. The post-operative follow-up was 13 to 44 months (mean 33.6 months). Results: Of 17 patients undergoing simultaneous bilateral EX-DCR with a mean age of 42.8 years, one of the patients had a history of bilateral unsuccessful DCR performed in a different center. One patient had previously failed bilateral probing before undergoing bilateral EX-DCR. This latter patient was a four-month-old baby with bilateral dacryoceles. Bicanalicular silicone intubation was performed in 15 eyes of 10 patients that had a canalicular problem or fibrotic lacrimal sac. It has been discerned that complaints about epiphora disappeared in 33 of the eyes (97%) and that the passage was open during the lacrimal irrigation. One eye with a history of unsuccessful dacryocystorhinostomy failed to respond positively to our operation. Conclusions: In our study, high success rates of simultaneous bilateral EX-DCR were found in both children and adult patients with bilateral dacryostenosis during a long-term follow-up. We believe that simultaneous bilateral dacryocystorhinostomy has medical, social, and economic advantages.